Strategi pengoptimalan pemanfaatan digital marketing dalam pengembangan Usaha Mikro Kecil dan Menengah (UMKM) - Septiana, Yuvi Putri (Maliki Interdisciplinary Journal, 2023)
The development of technology and the internet occurs in all areas of life, including in the economic field with the introduction of the term digital marketing. Digital marketing has a very important role in economic progress in this modern era, especially for Micro, Small and Medium Enterprises (MSMEs). With digital marketing, MSMEs can reach a wider target market and develop their business, as well as facilitate product promotion and marketing. Therefore with the method of literature review by collecting data from related literary sources with regard to writing problems. With this article, the author will provide several digital marketing introduction strategies that can be carried out as a MSME development strategy. Strategies for optimizing the use of digital marketing to develop MSMEs can be carried out by directing new forms of marketing strategies, drafting digital marketing methods, and providing assistance and education on the use of applications and social media for digital marketing media.